Development of an International Nursing College Model in Thailand - Nirotnun, Urai; Prachyayapruit, Apipa; Methakunavudhi, Pateep (Journal of The Royal Thai Army Nurses, 2020)
The purposes of this study were 1) To analyze situation of international nursing education in Thailand. and the good practices of nursing education management in overseas. 2) To analyze the need assessment for preparation to be an international nursing college in Thailand 3) To develop an international nursing college model in Thailand. and 4) To propose policy recommendations and practices for international nursing education management in Thailand. The samples were comprised of nursing instructors, international nursing students and Thai nursing students in international bachelor program in nursing, and experts in international nursing education. The research instruments were content analysis form and questionnaires. The data were analyzed by using frequency, percentage, mean, standard deviation and Modified Priority Needs Index (PNImodified ) analysis. The research findings were as follows; 1) The undergraduate international nursing education in Thailand was established as faculties under public and private university, as that stated vision on internationalization and have collaborations with International academic institutes. The good practices for nursing education management in overseas were comprised of the philosophy of being the world leader in education, research and academic services, the missions to integrate scholarship, research, education and practice and the teaching -learning management based on evidence-based practice, inter- professional education, web-based online learning, simulation based-learning. 2) Remarks from need assessment in preparation for establishing international nursing colleges in Thailand from the perspectives of both nursing instructors and students were as follows: 1) Arranging student exchange with overseas academic institutions, 2) Study in abroad as a part of the educational program, 3) Arranging joint program with international academic institutions, 4) Setting flexible financial and budget management to promote International nursing education management, 5) Arranging faculty exchange with international institutions. 3) An international nursing college model in Thailand composed of rationale, philosophy, vision, missions, goals, organization structures, and 3 important components. The first component was national and institutional enable factors. The national factors were: 1) Building alliances, 2) Income generation and commercial trade, 3) National enable and institutional collaboration and 4) Social and cultural development and mutual understanding. The institutional enable factors were: 1) International profile and reputation, 2) Quality enhancement and international standards, 3) Student and staff development and 4) Research and knowledge production. The second component was educational management which included curriculum, teaching and learning methods, students, and instructors. The third component was administration and management included resources, building, budget and finance and supporting staff. 4) Policy recommendations for an international nursing college management in Thailand should focus on: 1) Organization structures and international standard, 2) Memorandum of agreement, 3) Cost analysis, income generation and budget, 4) Faculty preparation, curriculum management, teaching and learning method, staff and environment preparation.